2021
DOI: 10.24815/siele.v8i1.18130
|View full text |Cite
|
Sign up to set email alerts
|

Exploring ESL learners' reading test taking strategies

Abstract: This study examined the test taking strategies of weak ESL students of an English language proficiency course. Test taking strategies are known as the methods that test takers use as an alternative aimed at attaining correct answers on a specified form of language assessment. The study adopted a qualitative study. The participants in this study were forty-four learners from the Bachelor of Arts Program. The learners were asked to think aloud while reading an assigned text to answer the questions. Four learners… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…They used memory strategies most frequently because understanding the reading texts may be one of the key strategies to do the reading tests effectively. This finding resonates with the theory claimed by scholars (e.g., Ellis et al, 1995;Phakiti, 2008;Singh et al, 2021) who have stated that test-takers use memory strategies to recall their prior knowledge of vocabulary and grammar to understand the reading texts. In terms of cognitive strategies, the findings showed that cognitive strategies were used at the second highest frequency, which may imply that participants may be aware of the importance of cognitive strategies and deployed them to construct the meaning from the reading texts.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…They used memory strategies most frequently because understanding the reading texts may be one of the key strategies to do the reading tests effectively. This finding resonates with the theory claimed by scholars (e.g., Ellis et al, 1995;Phakiti, 2008;Singh et al, 2021) who have stated that test-takers use memory strategies to recall their prior knowledge of vocabulary and grammar to understand the reading texts. In terms of cognitive strategies, the findings showed that cognitive strategies were used at the second highest frequency, which may imply that participants may be aware of the importance of cognitive strategies and deployed them to construct the meaning from the reading texts.…”
Section: Discussionsupporting
confidence: 88%
“…It is probable that the participants may recognize the significance of making clear plans and goals while doing their tests, which is supported by the claims of scholars (Karbalaei, 2010;Jafarigohar (2014;Sheorey & Mokhtari, 2001) indicating that test-takers need to self-control and self-regulate what they are reading for reading comprehension accomplishment. As for affective strategies; the result suggested that the EFL learners in MCB English Center used affective strategies at a high level, which further confirms that affective strategies are one of the common strategies deployed by test-takers when they do tests (e.g., Dreyer & Oxford, 1996;Oxford, 1990;Singh et al, 2021). This finding may imply that participants may also encounter different affective factors while doing reading tests, so they might have to deploy affective strategies to cope with negative emotions.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…The results of the research show that of all kinds of cognitive strategies, the strategy of using resources (English films) for receiving and sending messages is the strategy which has the highest number of users. In cognitive strategies, the students tend to use the strategy of using resources for receiving and sending messages (Hashim et al, 2018;Singh et al, 2021). Besides films, there are other resources that are used by the students are English programs on TV and radio, songs, and dictionary.…”
Section: Discussionmentioning
confidence: 99%